Адміністративно-правові засади запобігання корупційним та пов’язаним з корупцією правопорушенням - Василенко, О. Ю. (ДВНЗ «Ужгородський національний університет», 2023)
Дисертаційну роботу присвячено комплексному дослідженню адміністративно-правових засад запобігання корупційним та пов’язаним з корупцією правопорушенням, їх сучасного стану та можливостей вдосконалення з урахуванням практики правозастосування та зарубіжного досвіду. З’ясовуються поняття та виділяються ключові сутнісні характеристики, за якими розмежовуються безпосередньо корупційні правопорушення та пов’язані з корупцією правопорушення, а саме: 1) наявність / відсутність ознак корупції у вчиненому діянні (у випадку корупційного правопорушення мають місце ознаки корупції тоді, як пов’язане з корупцією правопорушення не містить ознак корупції, але порушує встановлені Законом України «Про запобігання корупції» вимоги, заборони та обмеження); 2) належність особи, що вчинила діяння, до переліку суб’єктів, на яких розповсюджується дія Закону України «Про запобігання корупції» (стосовно конкретних обмежень / вимог / заборон беруться до уваги окремі пункти переліку згідно цього Закону), та інші. Формулюється значення запобігання корупційним та пов’язаним з корупцією правопорушенням у вузькому та широкому розумінні. З’ясовується основа міжнародно-правового регулювання та національного законодавства щодо запобігання корупційним та пов’язаним з корупцією правопорушенням становлять положення. Обґрунтовується, що сучасний стан національного законодавства щодо запобігання корупційним та пов’язаним з корупцією правопорушенням характеризується наступними рисами: 1) декларативний характер положень антикорупційного законодавства та низький рівень їх фактичного впровадження і додержання; 2) недостатнє виконання системою законодавства щодо запобігання корупційним та пов’язаним з корупцією правопорушенням своєї превентивної ролі; 3) поспішне й неузгоджене прийняття нових нормативно-правових актів, що регулюють діяльність антикорупційних органів, що досить часто змінюються, тощо. Виявляються недоліки та прогалини в адміністративно-правовому регулюванні обмежень щодо використання службових повноважень чи свого становища, а саме наступні: 1) викликає сумніви, що особи, зазначені в п.4 ч.1. ст.3 Закону України «Про запобігання корупції», підпадають під обмеження у використання службових повноважень чи свого становища, адже вони лише «кандидати» на заняття посади, тобто власне службових повноважень відповідно саме для цих посад ще не набули; 2) адміністративно-правовими нормами, що регламентують дані обмеження, офіційно не трактуються поняття службових повноважень і становища, тощо. Узагальнюються особливості адміністративно-правового регулювання обмежень щодо сумісництва та суміщення з іншими видами діяльності, якими є наступні: 1) поширюються на осіб, зазначених у п.1 ч.1 ст.3 Закону України «Про запобігання корупції» (не залежно від того, перебувають вони в відпустці чи ні і т.п.); 2) полягає у забороні займатися іншою оплачуваною або підприємницькою діяльністю (за умови одержання прибутку) (винятки – викладацька, наукова та творча діяльність, медична практика, інструкторська та суддівська практика із спорту) та входити до складу правління, інших виконавчих чи контрольних органів, наглядової ради підприємства або організації, що має на меті одержання прибутку; 3) не є правопорушенням, пов’язаним із корупцією, отримання із запізненням винагороди / оплати за «іншу діяльність», яка була завершена до вступу на державну службу, тощо. Визначаються напрямки вдосконалення засад адміністративної відповідальності за вчинення пов’язаних з корупцією правопорушень в Україні, а саме наступні: 1) узгодження та уточнення норм КУпАП щодо адміністративної відповідальності за вчинення пов’язаних із корупцією правопорушень з метою підвищення їх ефективності; 2) розширення кола суб’єктів і деталізації об’єктів адміністративної відповідальності (порушення норм ст. 26 Закону України «Про запобігання корупції» та ін.) задля уникнення неоднозначного правозастосування та ухилення від відповідальності, у т.ч. народними депутатами; 3) встановлення адміністративної відповідальності за вчинення пов’язаних із корупцією правопорушень для юридичних осіб, та інші. The thesis is devoted to a comprehensive study of the administrative and legal foundations of the prevention of corruption and corruption-related offenses, their current condition, and opportunities for improvement, taking into account the practice of legal application and foreign experience. Concepts are clarified and key essential characteristics are distinguished, according to which corruption offenses and corruption-related offenses are directly distinguished, namely: 1) presence / absence of corruption features in the committed act (in the case of a corruption offense, signs of corruption occur whilst an offense related to corruption does not contain signs of corruption, but violates the requirements, prohibitions, and restrictions established by the Law of Ukraine "On Prevention of Corruption"); 2) belonging of the person who committed the act to the list of agents to which the Law of Ukraine "On the Prevention of Corruption" applies (regarding specific restrictions / requirements / prohibitions, individual items of the list are taken into account according to this Law), and others. The main types of corruption and corruption-related offenses are defined, namely: 1) violation of restrictions on the powers of authorities use or one’s position and restrictions after the termination of activities related to the performance of functions of the state, local self-government; 2) violation of restrictions and requirements regarding the receipt of illegal benefits or gifts and their handling; 3) violation of restrictions on compatibility and combination with other types of activities and joint work of close persons, and others. Benefits and drawbacks in the administrative and legal regulation of restrictions on the powers of authorities use or one’s position are revealed, namely the following: 1) it is doubtful that the persons specified in clause 4 part 1 of Article 3 of the Law of Ukraine "On the Prevention of Corruption" are subject to restrictions on the use of powers of authorities or their rank, because they are only "candidates" for occupying a position, that is, they have not yet acquired official powers, respectively, for these positions; 2) the concepts of official powers and ranks, etc., are not officially interpreted by the administrative and legal norms regulating these restrictions. As a result of the study of the administrative and legal regulation of restrictions on the receipt of unlawful benefits or gifts and their treatment, certain issues have been emphasized within this sphere: 1) the provisions of Part 1 of Art. 23 of the Law of Ukraine "On Prevention of Corruption", the effect of which currently applies only to the persons indicated in clauses 1-2 of part 1 of Article 3 of the Law and does not apply to clauses 3-4 (persons who permanently or temporarily hold positions related to the performance of organizational-administrative or administrative-economic duties, candidates for People’s Deputies of Ukraine, candidates for the post of President of Ukraine, etc.); 2) the issue of numerous cases of recognition of the insignificance of offenses related to the violation of the restriction on receiving gifts, which determines the improvement of the administrative and legal regulation of this area, etc., is urgent. The peculiarities of the administrative and legal regulation of restrictions on compatibility and combination with other types of activities are generalized, which are the following: 1) relate to the persons specified in clause 1, part 1, Article 3 of the Law of Ukraine "On Prevention of Corruption" (regardless of whether are they on vacation or not, etc.); 2) consists in the prohibition to engage in other paid or entrepreneurial activities (in case of receiving an income) (exceptions are teaching, scientific and creative activities, medical practice, instructor and referee practice in sports) and to be a member of the board, other executive or control bodies, supervisory the board of an enterprise or organization that aims to make a profit; 3) is not an offense related to corruption, late receipt of remuneration / payment for "other activity" that was completed before entering the public service, etc. A clarification of the concept of administrative and legal regulation of restrictions on the joint work of relatives is offered. It is ascertained that the norms of administrative law, which establish restrictions on the joint work of close people, the procedure for its application and the procedure for bringing to responsibility in case of its violation (in particular, the terms of bringing to administrative responsibility, the amount of fines, etc.), need to be revised and enhanced. The paths for improving the principles of administrative responsibility for committing corruption-related offenses in Ukraine are determined, namely the following: 1) coordination and clarification of the Code of Ukraine on Administrative Offenses norms regarding administrative responsibility for committing corruption-related offenses in order to increase their effectiveness; 2) expansion of the range of subjects and specification of objects of administrative responsibility (violation of the provisions of Article 26 of the Law of Ukraine "On Prevention of Corruption", etc.) in order to avoid ambiguous enforcement and deviation of responsibility, including People’s Deputies; 3) establishment of administrative responsibility for committing corruption-related offenses for legal entities, and others.
Administrative and legal grounds for preventing corruption and corruption-related offence
Keywords: адміністративно-правові засади; запобігання корупційним правопорушенням; корупційні правопорушення